Pricing and promotion effects on low-fat vending snack purchases: the CHIPS Study. - French, S A (2001)
OBJECTIVES: This study examined the effects of pricing and promotion strategies on purchases of low-fat snacks from vending machines. METHODS: Low-fat snacks were added to 55 vending machines in a convenience sample of 12 secondary schools and 12 worksites. Four pricing levels (equal price, 10% reduction, 25% reduction, 50% reduction) and 3 promotional conditions (none, low-fat label, low-fat label plus promotional sign) were crossed in a Latin square design. Sales of low-fat vending snacks were measured continuously for the 12-month intervention. RESULTS: Price reductions of 10%, 25%, and 50% on low-fat snacks were associated with significant increases in low-fat snack sales; percentages of low-fat snack sales increased by 9%, 39%, and 93%, respectively. Promotional signage was independently but weakly associated with increases in low-fat snack sales. Average profits per machine were not affected by the vending interventions. CONCLUSIONS: Reducing relative prices on low-fat snacks was effective in promoting lower-fat snack purchases from vending machines in both adult and adolescent populations.